Novel function of Oncostatin M as a potent tumour‐promoting agent in lung. Issue 4 (7th July 2014) - Lauber, Sean; Wong, Steven; Cutz, Jean‐Claude; Tanaka, Minoru; Barra, Nicole; Lhoták, Šárka; Ashkar, Ali; Richards, Carl Douglas
<x xml:space="preserve">Abstract</x> Oncostatin M is a leukocyte product that has been reported to have anti‐proliferative effects directly on melanoma and other cancer cell lines in vitro. However, its function(s) in cancers in vivo appears complex and its roles in cancer growth in lungs are unknown. Here, we show that OSM promotes marked growth of tumour cells in mouse lungs. Local pulmonary administration of adenovirus vector expressing mouse OSM (AdOSM) induced >13‐fold increase in lung tumour burden of ectopically delivered B16‐F10 melanoma cells in C57BL/6 mice. AdOSM caused increases in tumour size (14 days post‐challenge), whereas control vector (Addel70) did not. AdOSM had no such action in C57BL/6 mice deficient in the OSM receptor beta chain (OSMRβ−/−), indicating that these effects required OSMRβ expression on non‐tumour cells in the recipient mice. AdOSM induced elevated levels of chemokines and inflammatory cells in the bronchoalveolar lavage (BAL) fluid, elevated arginase‐1 mRNA levels (60‐fold), and increased arginase‐1+immunostaining macrophage numbers in lungs. Adherent BAL cells collected from AdOSM‐treated mice expressed elevated arginase‐1 activity. In contrast to AdOSM‐induced effects, pulmonary over‐expression of IL‐1β (AdIL‐1β) induced neutrophil accumulation and iNOS mRNA, but did not modulate tumour burden. AdOSM also increased lung tumour load (>50‐fold) upon ectopic administration of Lewis lung carcinoma (LLC) cells in vivo. However, in vitro, neither recombinant OSM nor AdOSM infection stimulated B16‐F10 or LLC cell growth directly. We conclude that pulmonary over‐expression of OSM promotes tumour growth, and does so through altering the local lung environment with accumulation of M2 macrophages.